Increasing Rice Harvest Yields in the Karang Rejo Village Community in Simalungun Regency - II, Harianto (International Journal of Educational Research Excellence, 2023)
Enhancing rice production in rural Indonesian communities requires comprehensive community development approaches that address technical, social, and economic constraints. This qualitative study examined community development initiatives aimed at improving rice harvest yields (dedeng panen) among farmers in Karang Rejo Village, Simalungun Regency, North Sumatra Province. Through in-depth interviews, focus group discussions, and participatory observation with 45 farmers and 12 key community stakeholders over a six-month period, this study explored multidimensional challenges and opportunities in rice productivity enhancement. The findings revealed that successful rice yield improvement requires integrated interventions to address technical knowledge gaps, input accessibility, infrastructure development, and institutional strengthening. Community-based approaches demonstrated significant improvements in rice productivity (38.1% increase in yield per hectare), farmer income (62.5% increase), and overall food security (30.8% improvement). The study identified critical success factors, including farmer group empowerment, agricultural extension services, demonstration plots, and improved access to quality input and credit facilities. These findings contribute to the understanding of effective community development strategies for sustainable agricultural improvement in Indonesian rural contexts, emphasizing the importance of participatory approaches that build local capacities while addressing systemic production constraints